2017
DOI: 10.5539/mas.v11n11p96
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Marketing Mix on Perceived Value, Destination Image and Loyalty of Tourists (Case Study: Khalkhal City, Iran)

Abstract: This study examines the relationship between marketing mix with loyalty, perceived value, perceived quality and destination image. This is an applied descriptive study the aim of which is to determine the impact of marketing mix of services (Product, Pricing, Place, Promotion, People, Process and Physical Evidence) on perceived quality, loyalty, perceived value and destination image of the tourists in Khalkhal city, Iran. Population of the study included all the tourists visiting Khalkhal city from among whom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…As the tourism activity has developed very quickly, there are currently a very limited number of products and they are of low quality. ESMAILI et al (2017) investigated the relationship between some elements of marketing mix with loyalty, perceived quality and destination image and reported that price in marketing mix had a positive impact on quality and loyalty while it had negative impact on the destination image. In the present study, visitors stated that there was no balance between quality and price.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As the tourism activity has developed very quickly, there are currently a very limited number of products and they are of low quality. ESMAILI et al (2017) investigated the relationship between some elements of marketing mix with loyalty, perceived quality and destination image and reported that price in marketing mix had a positive impact on quality and loyalty while it had negative impact on the destination image. In the present study, visitors stated that there was no balance between quality and price.…”
Section: Resultsmentioning
confidence: 99%
“…When it comes to service marketing where rural tourism is concerned, it is suggested that the 4Ps strategy should be extended to 7Ps or 8Ps. Based on a study by BOTTEN & MCMANUS (1999), ESMAILI et al (2017 express service marketing variables as seven strategic factors (7Ps) with an additional 3 Ps, as follows: physical evidence, people and process, or 8Ps including political and social situation (ESMAILI et al, 2017). Marketing mix model with these elements is studied in order to evaluate and prioritize the effective indices in rural tourism marketing as affecting factors of loyalty to a tourism destination (GHADIRI et al, 2013;ESMAILI et al, 2017).…”
Section: Marketing MIXmentioning
confidence: 99%
See 3 more Smart Citations